Bringing War to Book Writing and Producing the Military Memoir - Woodward, Rachel (Palgrave Macmillan UK, 2018)
This book explores how military memoirs come to be written and published. Looking at the journeys through which soldiers and other military personnel become writers, the authors draw on over 250 military memoirs published since 1980 about service with the British armed forces, and on interviews with published military memoirists who talk in detail about the writing and production of their books. A range of themes are explored including: the nature of the military memoir; motivations for writing; authors' reflections on their readerships; inclusions and exclusions within the text; the memories and materials that authors draw on;the collaborations that make the production and publication of military memoirs possible; and the issues around the design of military memoirs' distinctive covers. Written by two leading commentators on the sociology of the military, Bringing War to Book offers a new and original argument about the representations of war and the military experience as a process of social production. The book will be of interest to students and scholars across a range of disciplines including sociology, history, and cultural studies. .